THE USE OF INSTAGRAM IN TEACHING WRITING DESCRIPTIVE TEXT - Wahyuni, Siti Febry; Arifin, Zainal; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The research investigated the result whether implementing Instagram as a teaching media was effective in teaching students writing descriptive text or not. This was a pre-experimental research with one group pre-test and post-test design. There were 30 students of X Tata Niaga learning group who participated in this research. The date were collected by objective test and analyzed by t-test and effect size formula. According to the research findings, the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. The obtained t-value (3.615) was bigger than the critical value of r (1.699) by the degree of freedom 29. The effect size was categorized as strong effect since the ES value was 0.65 and bigger than 0.6. Everything considered, teaching writing descriptive text through Instagram, is significant and effective to year â€“ 10 of â€œSMK Panca Bhaktiâ€ in Academic Year 2018/2019. Â Keywords: Descriptive Text, Instagram, Writing.